(untitled) (Journal of Psychiatrists’ Association of Nepal, 2014)
Aim and Objectives: To study the socio-demographic and clinical profile of patients with chronic migraine headache, and to study the frequency and pattern of co-morbid psychiatric illnesses amongst these patients. Methodology: The study was done at the headache clinic in the Department of Psychiatry at Universal College of Medical Sciences, Bhairahawa, Nepal. All out-patients attending our clinic over a period of three months and aged between 15 to 55 years with a diagnosis of chronic migraine headache were included in the present study. Demographic and clinical profiles of these patients were noted in a specially designed socio-demographic and clinical data sheets prepared for the present study. Schedules for Clinical Assessment in Neuropsychiatry (SCAN) was used as diagnostic instrument; Hamilton Rating Scales for Anxiety & Depression (HAM-A, HAM-D) were used to rate the severity of Anxiety and Depressive symptoms. Simple statistical procedures like frequency, percentages, ‘t’-tests and chi-square tests were used for analysis of data thus obtained. Results: A total no of 48 cases of chronic migraine were included in the present study. Forty one cases (85.4%) were female and rest 7 patients were male. Comorbid psychiatric illness was present in thirty one (64.6%) cases among which Anxiety was the most common diagnosis (35.4%) followed by depressive disorders (29.2%). Conclusion: chronic migraine headache has high rate of co-morbid mood and anxiety disorder. Effective treatment of chronic migraine headache requires screening and accurately diagnosing specific psychiatric disorders when present. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11345 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 3-9